Shifts in Pharma-Marketing Trends in Post COVID-19 Era - Khan, Md. Mahfuzur Rahman; Basak, Kona (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study reveals that there will be shift in pharma-marketing trends in post COVID-19 era. The crisis of COVID-19, which responded in lockdowns and social distancing, highlighted in some key elements in the digital transformation of healthcare. Therewith the marketing techniques changes totally in the field of pharmaceuticals. As, this is an explorative research so qualitative data has been used for conducting the research. Secondary sources of data are used for analysis and interpretation and to develop the theoretical framework. Deductive approach is used in reaching the conclusive decision. Review of literature asserted about negative impacts of disruptions throughout the pandemics in past, yet these disruptions have also created some new opportunities. So to survive and to sustain pharmaceutical field and conjugate industries should now focus more on new marketing tactics, to counter COVID-19 side effects. Findings of the study educe that pharmaceutical industry could encounter the global pandemic by the shifts in pharma marketing strategies including advanced marketing, digital marketing, e-detailing customer relationship management, e-sampling, innovative work behavior, telemedicine revolution in order to promote product value and expediting prescriptions to the target consumer. So, coping up with the new normal and digitalizing the possible aspects of health care and medicines including techniques of pharma-marketing can be advantageous for both individuals and organizations.